In vitro activity of cefpodoxime against Russian clinical isolates of Haemophilus influenzae, Streptococcus pneumoniae and Streptococcus pyogenes - Kozlov R.S.; Ivanchik N.V.; Skleenova E.Yu.; Mikotina A.V.; Azyzov I.S.; Trushin I.V.; Dekhnich A.V. (Клиническая микробиология и антимикробная химиотерапия, 2023)
Objective.